Effect of aging heat treatment on corrosion behavior and corrosion kinetics of 17-4PH stainless steel in artificial saliva - Onthida Kosasang; Manutchaya Wongkaewmoon; Somwan Chumphongphan (Penerbit Universiti Kebangsaan Malaysia, 2021)
The corrosion behavior of the sintered 17-4PH stainless steel samples aged at different conditions in artificial saliva was studied using the method of electrochemical and weight loss after exposure for various periods of time. The results showed that the samples aged at 480 °C for 1 h exhibited the highest corrosion resistance. The pitting corrosion was predominantly initiated from existing, isolated pores and further accelerated. The corrosion kinetics trend is found to be more consistent with a bimodal function form rather than the classical power-law function.